Turning crisis into potential: Leveraging the skills of forced Ukrainian migrant women in Poland - José Enrique Castillo-Sánchez; Paul Phumpiu Chang; Agnieszka Olter-Castillo (PLoS ONE, 2026)
The 2022 Russian invasion of Ukraine triggered a large influx of highly skilled Ukrainian women into Poland, presenting both challenges and opportunities for their effective economic integration. This study employs network analysis on firm-level data from the Orbis database to identify 32 key industries – including food manufacturing, textiles, business services, wholesale trade, and healthcare – where Ukrainian managerial talent can enhance Poland’s industry space. Guided by a conceptual framework of three mechanisms for integration – (1) Matching and Complementarities, (2) Diversification via Relatedness, and (3) Gendered Sectoral Constraints – we examine how sectoral skill alignment interacts with gendered barriers to shape integration outcomes. By examining industry specialisation patterns and gender dynamics, we assess how leveraging the expertise of these skilled migrant women can drive economic diversification, fill labour shortages, and stimulate innovation. Our findings underscore that these women can strengthen market competitiveness in industries where Poland has a specialisation advantage and contribute to economic diversification in emerging industries – provided that gender-specific barriers are addressed. This study contributes to the broader discourse on migration, gender, and industrial policy, offering an empirical framework for other host countries seeking to transform skilled refugee inflows into engines of economic growth. The findings emphasise the necessity of evidence-based policies that align skilled migration integration strategies with industrial and gender equity objectives to maximise economic benefits.